Building Information Modeling (BIM) Technology Acceptance Analysis Using Technology Acceptance Model (TAM) - Felix Andrian Prihatono; Tri Joko Wahyu Adi (Institut Teknologi Sepuluh Nopember, 2020)
The growth of an industry growth couldn’t be separated from technology development. Nowadays, technology development mostly affected by digitalization, which brought us to industry 4.0 era. The same thing also occurs in construction industry, although its development relatively slower than the growth in manufacturing industry. Construction technology, such as Building Information Modeling (BIM), 3D printing, and robotic equipments, has been introduced to construction industry. BIM is defined as digital representation of physical and functional characteristics of a facility, forming a reliable basis for decisions during its life-cycle. However, in the end, technological development in Construction Industry depends on industry players’ readiness to accept and implement the most advance technology. This research’s focus is on BIM technology acceptance among players in Indonesia Construction Industry. The research will be conducted in Indonesia Construction Industry, data will be collected through questionnaires asked to the industry players, such as, consultants, project owners, and contractors who have already use BIM technology for their projects. The analysis will be conducted using Technology Acceptance Model (TAM). TAM is a model which was developed to enhance our understanding about user acceptance of a technology, thus could enable technology designer and implementator to evaluate the system before it being implemented. The research’s result shows that Indonesia Construction Industry is able to accept BIM technology, the conclusion is taken because all the variables used in TAM has higher than 3 on 1 to 5 Likert scale. Path analysis also shows that Attitude Toward Usage variable do not affect Behavioral Intention variable. Direct, Indirect, and Total Effects analysis show that BIM technology acceptance is affected by Perceived of Usefulness. This result could be used as a basis to introduce BIM to new users, that people are more interested in its usefulness rather than ease of use variable.